Financial health protection in Swaziland: an assessment of financial catastrophe and impoverishment from out-of-pocket payments - Ngcamphalala, Cebisile (Health Economics Unit, 2016)
As the drive towards universal coverage is gaining momentum globally, the need for assessing levels of financial health protection in countries, particularity the developing world, has increasingly become important. Swaziland's health financing system performance in terms of ensuring financial health protection is not clearly understood. This paper assesses financial catastrophe and impoverishment from out - of - pocket payments and associated factors that predict them in Swaziland. The Swaziland Household Income and Expenditure Survey (SHIES) for 2009/2010 was used for the analyses. Financial catastrophe was assessed using a variable threshold. Impoverishment was assessed using both a national and $1.25/day international poverty line. Logistic regression models were used to assess factors that predict household vulnerability to financial catastrophe and impoverishment. It emerged that about 9.6 per cent of the Swazi households experienced financial catastrophe while about 1.1 per cent were pushed below the poverty line as a result of out - of - pocket payments. Factors associated with households' vulnerability include; education of the household - head, household size, location, age and household socio - economic status. The findings indicate that financial health protection is not adequate in Swaziland. Thus, there is a need for financing mechanisms that do not place undue hardships on the poor and vulnerable.